A Preliminary Study Of Lipid Profiles In Pediatric Population And Youth Population With Type I Diabetes - K.KANAGALAKSHMI M.SC,; M.PHIL,; MAZHER SULTANA, (International Journal of Pharma and Bio Sciences, 2012)
The term diabetes usually refers to diabetes mellitus, which roughly translates to excessive sweet urine. Diabetes mellitus (DM) is a chronic disease which leads to biochemical and anatomical/structural consequences. It is a disease of carbohydrate, fat, and protein metabolism caused by the lack of insulin, which results from the marked and progressive failure of the pancreas to secrete insulin because of autoimmune destruction of the beta cells. The purpose of this study is to identify the role of glycemic control on the altered lipid profile in pediatric population and youth population with Type I diabetes of poverty line attending to Government Stanly Hospital, Chennai